Selection and Production of a Suitable Support for Palladium Membranes (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The present work focuses on establishing anactual manufacturing strategy that is suitable for the viableproduction of a substrate support for a palladiummembrane; one that will lower production costs and beutilised to gain a competitive edge within the industry.Porous stainless steel supports for palladium membraneswere produced using various types of stainless steel powdersand methods. Observations indicate that SS powder 410Ltype Chengdu Huarui with particle sizes 1-5 μm, sintered inthe HPT induction furnace at temperatures between 930-950°C for a period of 8 minutes, in the presence of argonflow and vacuum, creates a first-class Pd membranesubstrate. Notwithstanding that this result is the mosteconomical method. The results of the study were based onthe: roughness test, first bubble point test, and scanningelectron microscope (SEM). The Chengdu Huarui powdertype 410 L – 1-5 μm, which achieved the best results,produced a roughness test result of Ra 0.614 μm, and abubble point pore size is 1.992 μm.